Teen Titans : Robin - Garcia, Kami (DC Comics, 2023)
Raven Roth, Garfield Logan, Maxine Navarro, and Damian Wayne are on the run, while Dick Grayson wants to know what happened to his brother, Damian, and they all want to defeat H.I.V.E. for good.